STRATEGI PROMOSI EKOWISATA MANGROVE PANDANG TAK JEMU DI KOTA BATAM - Zakyya, Tassya; Cindo, Ageng Rara Cindoswari (SCIENTIA JOURNAL, 2024)
Communication has an important role for the development of tourism, especially in Batam City. In introducing ecotourism potential to tourists, in addition to good management of tourist attractions, creative and effective promotion is also needed. In this study to conduct tourism promotion, researchers used an integrated marketing communication approach or (Integrated Marketing Communication) IMC. The purpose of this study is to find out what communication strategies are appropriate for pokdarwis to use in promoting Pandang Tak Jemu Mangrove Ecotourism. carried out with a qualitative descriptive approach. Qualitative methods are carried out through interview techniques to resource persons by limiting interview points to relevant topics. Sampling through snowball sampling method is purposive until the data collected is considered representative. In addition to interviews, the author also made direct observations around tourist destinations and used documentation of data sources in the form of pictures of ecotourism activities, recordings and drawings, as well as records or recaps of pokdarwis activities. The result of this research is the application of elements of the promotion mix or (Mix Promotion) which includes: advertising (advertising), direct marketing (direct marketing), publicity (publicity), marketing (sponsorships), sales promotion (sales promotion). Keywords: Tourism Awareness Group (Pokdarwis), Integrated Marketing Communication, Promotion.